find the answer with explanation
Attachments:
![](https://hi-static.z-dn.net/files/d8f/b2c8ffbda4286fe4c4d9523c6ebfec36.jpg)
Answers
Answered by
1
Given ax=cq = b and cy =az = d
⇒ ax = b and cq = b
⇒ a = b1/x and c = b1/q
Now consider, cy = az = d → (1)
Now substitute the values of c and a in equation (1), we get
( b1/q)y = (b1/x )z = d
⇒ ( by/q) = (bz/x ) = d
Comparing both the sides, we get
(y/q) = (z/x)
⇒ xy = zq
Hence option (A) is correct.
i hope it will help u
⇒ ax = b and cq = b
⇒ a = b1/x and c = b1/q
Now consider, cy = az = d → (1)
Now substitute the values of c and a in equation (1), we get
( b1/q)y = (b1/x )z = d
⇒ ( by/q) = (bz/x ) = d
Comparing both the sides, we get
(y/q) = (z/x)
⇒ xy = zq
Hence option (A) is correct.
i hope it will help u
Similar questions